The Pastor’s Role in Effectively Managing the Congregation’s Potential: A Case Study in GKII Gracia Sintang - Herwinesastra, Herwinesastra; Luther, Henry; Rostiani, Rostiani (Sekolah Tinggi Teologi Simpson Ungaran, 2023)
This article examines the pastor's role as a religious leader in empowering the congregation's potential. Research for this article was conducted in GKII Gracia parish, Sintang. Qualitative method was utilized by the researchers, who interviewed the pastor, church committee members, and many members of the congregation. Data triangulation was used to obtain pertinent information from interview transcripts, and the results were then presented in a descriptive manner. Based on the collected data, these roles—which the pastor does in his capacity as a spiritual leader—were recognized as being essential to achieving church autonomy in GKII Gracia Sintang: 1) enlistment of the congregation in spiritual ministry to involve them according to their own abilities and potential, 2) optimization of external opportunities and utilization of internal potential to achieve good results, 3) mobilization of the congregation through encouraging and galvanizing them to participate in church ministry. In order to support these roles, particularly mobilization, training, pastoral visitation, and sermon delivery aimed at awakening the congregation to the importance of their participation were carried out.